2, 3‐Dihydroxy‐quinoxaline induces ATPase activity of Herpes Simplex Virus thymidine kinase. Issue 3 (25th December 2013) - Zeifman, Alexey A.; Novikov, Fedor N.; Stroylov, Victor S.; Stroganov, Oleg V.; Chilov, Ghermes G.; Skoblov, Alexander Y.; Miroshnikov, Anatoly I.; Skoblov, Yuri S.
Abstract : 2, 3‐Dihydroxy‐quinoxaline, a small molecule that promotes ATPase catalytic activity of Herpes Simplex Virus thymidine kinase (HSV‐TK), was identified by virtual screening. This compound competitively inhibited HSV‐TK catalyzed phosphorylation of acyclovir with K i = 250 μM (95% CI: 106–405 μM) and dose‐dependently increased the rate of the ATP hydrolysis with K M = 112 μM (95% CI: 28–195 μM). The kinetic scheme consistent with this experimental data is proposed. Abstract : 2, 3‐Dihydroxy‐quinoxaline inhibits acyclovir phosphorylation by herpesvirus thymidine kinase. 2, 3‐Dihydroxy‐quinoxaline promotes ATPase activity of herpesvirus thymidine kinase. This promotion is dose‐dependent and follows the Michaelis–Menten scheme. We propose a kinetic scheme for the whole process that is consistent with the experimental data.